Perancangan Sistem Informasi Pengelolaan Rencana Anggaran Biaya (RAB) Pada Perusahaan Konstruksi Berbasis Web (Studi Kasus CV. Osa Karya Mandiri) - Ni Komang Ayu Suarpurningsih; A.A Istri Ita Paramitha (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2021)
At present there are many construction companies spread across Indonesia, so they have competition both in terms of promoting their companies and in terms of bidding on the right and quality construction costs. CV. OSA Karya Mandiri is a construction company that was founded in 2015. The bid for construction costs is CV. OSA Karya Mandiri is currently still recorded manually and computerized using Microsoft Excel version 2010 software which causes many errors to be found in recording and calculating the RAB itself. In order to overcome this, it is necessary to create a system that makes it easier to calculate the budget plan for a construction project by the company. This study aims to design a web-based budget plan management system using the System Development Life Cycle (SDLC) method. The result of this study is an information system for managing budget plans (rab) in web-based construction companies (case study cv. osa Karya Mandiri).